The Association between Invasive Group A Streptococcal Diseases and Viral Respiratory Tract Infections - Herrera, Andrea L.; Huber, Victor C.; Chaussee, Michael S. (Frontiers in Microbiology, 2016)
Viral infections of the upper respiratory tract are associated with a variety of invasive diseases caused by Streptococcus pyogenes, the group A streptococcus, including pneumonia, necrotizing fasciitis, toxic shock syndrome, and bacteremia. While these polymicrobial infections, or superinfections, are complex, progress has been made in understanding the molecular basis of disease. Areas of investigation have included the characterization of virus-induced changes in innate immunity, differences in bacterial adherence and internalization following viral infection, and the efficacy of vaccines in mitigating the morbidity and mortality of superinfections. Here, we briefly summarize viral-S. pyogenes superinfections with an emphasis on those affiliated with influenza viruses.